Um testemunho (re)velado, uma forma de ler Maupassant - Lima, Clarissa Navarro Conceição [UNESP] (2017)
The Franco-Prussian War has left deep traces in the history of the French, who had their homeland invaded, bombed, humiliated and tortured. The conflict occurred from 1870 to 1871, although short, caused many deaths and much destruction. Guy de Maupassant took part in the war when he was young and about ten years later produces several narratives related to the historic moment of which he was also part. In his short stories of war, the historical memory is present and sustains the whole narrative; we reflected, therefore, in this work, the question of the testimony without an "i-witness". The author who has seen and experienced the catastrophe of war also offers his rightful testimony, even if it is masked by his images and comparisons. We try to prove that the testimony from the fiction can also be authentic, since, according to Seligmann-Silva and Octavio Paz, all truth is historical, all literature is testimonial and every testimony has the maximum credit of truth. For that, we count on the support of some theories already known, such as the analysis and the theoretical study of the work of Seligmann-Silva, such as those present in History, Memory and Literature: The testimony in the era of catastrophes, among others.